High prevalence of anti-CD74 antibodies specific for the HLA class II-associated invariant chain peptide (CLIP) in patients with axial spondyloarthritis. Issue 6 (3rd May 2013) - Baraliakos, X; Baerlecken, N; Witte, T; Heldmann, F; Braun, J
Abstract : Objectives: The pathogenesis of axial spondyloarthritis (axSpA) is still unclear. There is a strong association with HLA-B27 and other genes. Recently, anti-CD74 antibodies with specificity to a class II-associated invariant chain peptide (anti-CLIP-ABs) were found in axSpA patients. We examined the prevalence, sensitivity and specificity of anti-CLIP-ABs in axSpA in comparison with controls. Methods: Sera of axSpA and non-SpA patients were analysed for IgG-antibodies against CD74 by ELISA with specificity for CLIP developed in cooperation with AESKU Diagnostics (Germany). A cut-off of ≥4 SDs of arbitrary units (AU) from mean serum levels was used to differentiate the results. The laboratory workers were completely blinded for clinical data. Results: We analysed 145 sera from 94 axSpA and 51 non-SpA patients. AxSpA patients were more often male and younger. HLA-B27 status was available in 72 patients. Anti-CLIP-ABs were detected in 85.1% in axSpA but in only 7.8% in non-SpA patients (p≤0.0001). AxSpA patients showed higher levels of anti-CLIP-ABs versus non-SpA: mean 14.5 versus 0.8 AU (p≤0.0001). The sensitivity of anti-CLIP-ABs for diagnosing axSpA was 85.1%, specificity 92.2%, likelihood ratio (LR) LR+ was 10.8 and LR− was 0.08. Anti-CLIP-ABs and HLA-B27 were positive in 87.5% patients with axSpA, but only 14.9% were anti-CLIP-negative, while 23.6% were HLA-B27-negative. Conclusions: Anti-CLIP antibodies were strongly associated with axSpA. The LR for confirming axSpA by using anti-CLIP was even higher than by using HLA-B27. More studies using this promising new method in patients with non-radiographic axial SpA or peripheral SpA are needed to establish its usefulness in clinical practice.